A smart scale for efficient inventory management based on design science research principles - Tung-Hsiang Chou; You-Sheng Chen; Chung-Wei Pan; Hung-Hsuan Chang (Contemporary Economics, 2024)
Even in the context of Industry 4.0, conventional warehouse management continues to encounter challenges. Amidst these obstacles, innovative solutions are imperative. Order picking, a critical process with significant implications for customer service, remains labor-intensive within warehousing operations. Current manual methods result in prolonged inventory cycles and inherent accuracy complexities. To address these issues, this research has used the Design Science Research (DSR) method for developing a device called the Smart Scale, which helps optimize warehouse inventory management. This device, which is tailored specifically for lightweight items such as chewing gum, screws, and fasteners, uses weight sensors to calculate real-time quantities dynamically. By reducing human error and enhancing item supervision, the Smart Scale improves inventory precision and time and cost efficiencies.
Keywords: C80; L86; 330; Industry 4.0; DSR; IoT; intelligent warehousing; order picking